Clinical value of fecal calprotectin for evaluating disease activity in patients with Crohn’s disease - Li, Junrong; Xu, Mingyang; Qian, Wei; Ling, Fangmei; Chen, Yidong; Li, Shuang; Cheng, Yiyu; Zhu, Liangru (Frontiers in Physiology, 2023)
Objective: To explore the clinical value of fecal calprotectin (FC) for evaluating disease activity in patients with Crohn’s disease (CD) and its relationship with disease location. Methods: Patients with CD were enrolled retrospectively, and clinical data, including FC levels, were collected. Clinical activity was assessed using the Crohn’s disease activity index (CDAI). Endoscopic activity was assessed using a simple endoscopic score for Crohn’s disease (SES-CD). The partial SES-CD (pSES-CD) was scored for the size of ulcers in each segment as defined by the SES-CD and was calculated as the sum of segmental ulcer scores. Results: This study included 273 CD patients. The FC level was significantly positively correlated with the CDAI and SES-CD, with correlation coefficients of 0.666 and 0.674, respectively. The median FC levels in patients with clinical remission and mildly active and moderately–severely active disease were 41.01, 164.20, and 444.45 µg/g. These values were 26.94, 66.77, and 327.22 µg/g during endoscopic remission and mildly and moderately–severely active stages, respectively. Compared with c-reactive protein (CRP), the erythrocyte sedimentation rate (ESR), and other biomarker parameters, FC was better at predicting disease activity for CD patients. For an FC <74.52 µg/g, the area under the curve (AUC) for predicting clinical remission was 0.86, with a sensitivity of 89.47% and a specificity of 71.70%. Moreover, endoscopic remission was predicted with a sensitivity of 68.02% and a specificity of 85.53%. The AUC was 0.83, and the cutoff value was 80.84 µg/g. In patients with ileal and (ileo) colonic CD, FC was significantly correlated with the CDAI, SES-CD, and pSES-CD. The correlation coefficients were 0.711(CDAI), 0.473 (SES-CD), and 0.369 (pSES-CD) in patients with ileal CD and 0.687, 0.745, and 0.714 in patients with (ileo) colonic CD, respectively. For patients in remission, those in the active stage, and those with large or very large ulcers, differences in FC levels were not significant between patients with ileal and (ileo) colonic CD. Conclusions: FC is a reliable predictor of disease activity in patients with CD, including those with ileal CD. FC is thus recommended for the routine follow-up of patients with CD.